Produção e caracterização de compósitos com matrizes de gesso comum e reciclado e fibra de coco verde hornificada - Freitas, Michelline Nei Bomfim de Santana (2024)
The use of green coconut fibers as reinforcement in composites represents a viable application in economic, environmental and technological concepts. But as the fiber is hydrophilic and the matrices are hydrophobic, treatments are necessary for good fiber-matrix interaction, for example, hornification. Hornification consists of successive cycles of moistening and drying the fibers, which can reduce water absorption and dimensional instability, in addition to improving mechanical properties and the fiber-matrix bond. Gypsum is a binder widely used in construction, resulting in high waste generation. Therefore, recycling these materials is extremely important for sustainable development. The objective of this work was to produce and characterize composites with common gypsum matrices, recycled gypsum and reinforcement with hornified green coconut fibers. The composites were subjected to mechanical and morphological characterizations, in addition to determining their apparent densities and water absorption, they were also heated to 200°C and 400°C, and subjected to ultrasound tests. It was concluded that hornification changed the morphology of the fibers, their surfaces and cross-sections, promoted an increase in their tensile strength for 5 and 10 cycles, improved the thermal stability of the fibers, and reduced water absorption, without major changes in the crystallinity index and crystallite size. The best results were obtained in hornification in 10 cycles with distilled water. It can be seen that the incorporation of green coconut fibers into the plaster matrix caused a reduction in its mechanical performance, the higher the fiber content incorporated, the greater this reduction. This reduction was, on average, 26% for 5% fiber content, 37% for 10% fiber, and 52% for 20% fiber. Composites with higher fiber contents had lower apparent densities, higher water absorption and lower VPUs. The actions of heating at temperatures of 200°C and 400°C reduced the integrity of the composites.